1996
DOI: 10.2307/3433162
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the DNA Adducts Formed in B6C3F1 Mice Treated with Benzene: Implications for Molecular Dosimetry

Abstract: We have investigated the formation of DNA adducts in the bone marrow and white blood cells of male B6C3F1 mice treated with benzene using P1-enhanced 32P-postlabeling. No adducts were detected in the bone marrow of controls or mice treated with various doses of benzene once a day. After twice-daily treatment for 1 to 7 days with benzene, 440 mg/kg, one major (no. 1) and up to two minor DNA adducts were detected in both the bone marrow and white blood cells. The relative adduct levels in these cells ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Benzene yielded mixed results in genotoxicity test systems (International Agency for Research on Cancer, 2000b), with the exception of bone marrow. DNA binding was either absent or extremely low in several tissues in rats (Reddy et al, 1989), although binding was reported under extreme conditions (twice-daily treatment for 1 to 7 days with 440 mg/kg benzene) (Bodell et al, 1996). A scheme for the biotransformation of benzene based upon (Snyder and Hedli, 1996) is shown in Figure 19.…”
Section: Human Effects Of Rodent Nasal Cytotoxinsmentioning
confidence: 99%
“…Benzene yielded mixed results in genotoxicity test systems (International Agency for Research on Cancer, 2000b), with the exception of bone marrow. DNA binding was either absent or extremely low in several tissues in rats (Reddy et al, 1989), although binding was reported under extreme conditions (twice-daily treatment for 1 to 7 days with 440 mg/kg benzene) (Bodell et al, 1996). A scheme for the biotransformation of benzene based upon (Snyder and Hedli, 1996) is shown in Figure 19.…”
Section: Human Effects Of Rodent Nasal Cytotoxinsmentioning
confidence: 99%
“…39 Through their inhibitory action on topoisomerase II, binding to other DNA-associated proteins and formation of DNA adducts, phenol and hydroquinone cause double-strand breaks and chromosome breakage. 40,41 This has been shown in vitro to lead to deletions and translocations commonly found in leukemia, including del(5q) and del(7q). 38 Again, workers exposed to benzene have been shown to have higher levels of del(5q), del(7q) and translocation (8;21) in their blood cells.…”
Section: Figurementioning
confidence: 99%
“…DNA damage, formation of DNA adducts, chromosomal aberrations such as aneuploidy, increased formation of micronuclei and sister chromatid exchanges) of benzene and its metabolites (namely HQ, 1,4-BQ, 1,2,4-BT and catechol) is the most reported key event observed in the identified in vitro studies Bodell et al, 1996;Chung et al, 2002;Hedli et al, 1996;Ishihama et al, 2008;Levay & Bodell, 1992;Levay et al, 1993;Lindsey et al, 2005;Lindsey et al, 2004;Mondrala & Eastmond, 2010;Oikawa et al, 2001;Pandey et al, 2009;Pasquini et al, 2003;Thys et al, 2015;Winn, 2003;Zhang et al, 1993;Zhang et al, 1994;Zhang et al, 1998). Then it is followed by oxidative stress as an early key event associated with benzene and its metabolites (Badham & Winn, 2010a;Goldman et al, 1999;Ishihama et al, 2008;Kolachana et al, 1993;Li & Trush, 1993;Nishikawa et al, 2012;Oikawa et al, 2001;Ruiz-Ramos et al, 2005;Wan & Winn, 2007;Wiemels & Smith, 1999;Zhang et al, 1993).…”
Section: Supporting Publications 2016: En-955 129mentioning
confidence: 99%
“…not immortalised) cells Bodell et al, 1996;Chung et al, 2002;Irons et al, 1992;Levay et al, 1993;Thys et al, 2015;Zhang et al, 1998).…”
Section: Supporting Publications 2016: En-955 129mentioning
confidence: 99%